Least Significant Bit (LSB) and Random Right Circular Shift (RRCF) in digital watermarking - Kurdi, Moustafa M.; Elzein, Imad A.; Zeki, Akram M. (IEEE, 2016)
Digital watermarking is an authentication technique for distribution of content over the Internet. Such a method is highly desired due to the proliferation of high-capacity, digital recording contrivances which have fueled incremented concerns over copyright auspice of content 111. Digital Watermarks are valuable mechanisms for protecting image, audio, video, and data and they are withal becoming a consequential implement in facilitating e-commerce. Any company that is earnest ab out safely protecting and distributing their content and products must use digital watermarks. Digital watermarking and steganography is considered as the most interesting field of research and development for many authors. In this article, we use Least Significant Bit (LSB) and Random Right Circular Shift (RRCF) in digital watermarking. LSB is used because it is not noticeable by human eyes and of its minor distortion of the image. For simulation of our algorithm, we apply MA TLAB using Least Significant Bit (LSB) and Random Right Circular Shift (RRCF